LTE International Roaming Optimization Scheme Based on Equivalent PLMN - Jie Qin; Chen Fang; Haichen Liu; Wenbing Cheng; Bing Wu; Xiaozhi Pan; Riming Liang; Zhihua Chen (Dianxin kexue)
With the development of LTE international roaming, the long time delay for roaming network selection has recently attracted much attention. A LTE international roaming optimization scheme based on equivalent PLMN was investigated. By deploying the scheme in China Mobile Shenzhen Branch and HongKong Branch LTE networks at frontier ports area, UE can do reselection（in idle mode）and redirection（in connected mode）between cells from different operators across the boundary. The average no service time across the boundary shortened from 90 seconds to 5.96 seconds, the customer's international roaming perception was greatly improved.